Reinterpreting Muslim Women’s Fashion in Hadith: Between Religious Norms and Modern Lifestyle - Ahmad Bastari (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2026)
This study aims to examine the phenomenon of Muslim fashion trends among women from the perspective of the Prophet's hadith. Using qualitative methods with a descriptive-analytical approach, this study seeks to understand the dynamics of Muslim women's fashion practices in a contemporary social context. The results indicate that, from the perspective of the Prophet's hadith, following fashion trends is permissible as long as it does not conflict with Islamic law, which has established the principles of dress for Muslim women. The rapidly growing phenomenon of Muslim fashion trends, particularly through social media, reflects Muslim women's efforts to maintain a modern appearance without neglecting the obligation to cover their aurat (awrah). Islam, as a religion, provides normative guidelines regarding dress ethics, but does not prohibit Muslim women from following fashion trends as long as they remain within the boundaries of sharia. Therefore, this study recommends that Muslim women who wish to follow fashion trends continue to consider sharia values ​​as the primary basis for selecting and wearing clothing. This study contributes to bridging the relationship between religious norms and modern lifestyle practices, particularly in the phenomenon of Muslim women’s fashion. It demonstrates that there is a dialectical space between Sharia and modernity, allowing Muslim women to express their identity through clothing without departing from the fundamental principles of Islamic teachings.